Writing 1968: A Native American Perspective on the Nineteen-Sixties - Vincent Veerbeek (Università degli Studi di Torino, 2019)
One feature of United States public memory is the way in which it tends to neglect the Native American perspective on mainstream American history, regardless of their involvement. This holds true even for the nineteen-sixties, a decade that is generally seen as multi-faceted. Even if there are countless established memories of this well-remembered decade, however, the Native American narrative is not one of them. Using Vine Deloria’s Custer Died for Your Sins: An Indian Manifesto (1969) and We Talk, You Listen (1970), this paper will explore Native American understandings of the Vietnam War and the African American freedom struggle. Both were focal points of division in United States society at the time and have since come to define public memory of the nineteensixties, but are rarely considered from a Native American perspective.